Variation of 6-Methylaminopurine Content in Bacteriophage P22 Deoxyribonucleic Acid as a Function of Host Specificity - Hattman, Stanley (1971)
The 6-methylaminopurine (MAP) content of P22 deoxyribonucleic acid has been analyzed as a function of the host specificity it carries. A 40 to 50% reduction in MAP level occurs as a result of growth in host cells defective in the ability to confer LT specificity.